Zaman beredar pesaka bergilir Melayu dalam zaman peralihan (Kuala Lumpur Endowment Publication, 1999)
Socioeconomic and political conditions in Malaysia.
Includes bibliographical references and index.
Keywords: Malaysia -- Economic conditions; Malaysia -- Politics and government; Malaysia -- Social conditions